2020
DOI: 10.1111/eci.13388
|View full text |Cite
|
Sign up to set email alerts
|

Statins: Epidrugs with effects on endothelial health?

Abstract: Background: Epigenetic events involving the methylation of CpG cites in DNA, histone modifications and noncoding RNAs correlated with many essential processes in human cells and diseases, such as cancer and cardiovascular diseases. HMG-CoA reductase inhibitors (statins)-the LDL cholesterol-lowering drugs-are broadly used in cardio-and cerebro-vascular diseases. It is well established that statins exert pleiotropic functions, but how they exert effects on epigenetic modifications independently of HMG-CoA reduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 76 publications
0
14
0
Order By: Relevance
“…Lipid-lowering therapies, including 3-hydroxy-3-methyl-glutaryl-coenzyme A reductase inhibitors (i.e., statins) and proprotein convertase subtilisin/kexin type 9 inhibitors, reduce circulating levels of LDL-cholesterol and thus oxLDL in the vessel wall, and decrease the incidence of severe events in CVD ( Silverman et al, 2016 ; Mach et al, 2020 ), although these agents are not sufficient to prevent plaque formation ( Tran-Dinh et al, 2013 ; Moss and Ramji, 2016 ). Moreover, a spectrum of anti-atherogenic effects of statins on the endothelium has been previously discussed in detail ( Xu et al, 2021 ), and includes reduced inflammation through NF-κB blockade ( Greenwood and Mason, 2007 ), inhibition of EC apoptosis via Janus kinase 2/signal transducer and activator of transcription 3 signaling ( Wang K. et al, 2020 ), protection against EndMT via Kruppel-like factor 4/miR-483 ( He et al, 2017 ), epigenetic modulation of ECs through histone modification ( Mohammadzadeh et al, 2020 ), and increased NO production via hydrogen sulfide and eNOS ( Citi et al, 2021 ; Xu et al, 2021 ). Notably, the statin-mediated mechanisms that contribute to elevated eNOS activity include increased eNOS transcription via KLF2 ( Parmar et al, 2005 ), improved eNOS mRNA stability via polyadenylation ( Kosmidou et al, 2007 ), and increased eNOS phosphorylation via phosphatidylinositol 3-kinase/Akt signaling ( Kureishi et al, 2000 ).…”
Section: The Vascular Endothelium As An Emerging Therapeutic Target For Atherosclerosismentioning
confidence: 99%
“…Lipid-lowering therapies, including 3-hydroxy-3-methyl-glutaryl-coenzyme A reductase inhibitors (i.e., statins) and proprotein convertase subtilisin/kexin type 9 inhibitors, reduce circulating levels of LDL-cholesterol and thus oxLDL in the vessel wall, and decrease the incidence of severe events in CVD ( Silverman et al, 2016 ; Mach et al, 2020 ), although these agents are not sufficient to prevent plaque formation ( Tran-Dinh et al, 2013 ; Moss and Ramji, 2016 ). Moreover, a spectrum of anti-atherogenic effects of statins on the endothelium has been previously discussed in detail ( Xu et al, 2021 ), and includes reduced inflammation through NF-κB blockade ( Greenwood and Mason, 2007 ), inhibition of EC apoptosis via Janus kinase 2/signal transducer and activator of transcription 3 signaling ( Wang K. et al, 2020 ), protection against EndMT via Kruppel-like factor 4/miR-483 ( He et al, 2017 ), epigenetic modulation of ECs through histone modification ( Mohammadzadeh et al, 2020 ), and increased NO production via hydrogen sulfide and eNOS ( Citi et al, 2021 ; Xu et al, 2021 ). Notably, the statin-mediated mechanisms that contribute to elevated eNOS activity include increased eNOS transcription via KLF2 ( Parmar et al, 2005 ), improved eNOS mRNA stability via polyadenylation ( Kosmidou et al, 2007 ), and increased eNOS phosphorylation via phosphatidylinositol 3-kinase/Akt signaling ( Kureishi et al, 2000 ).…”
Section: The Vascular Endothelium As An Emerging Therapeutic Target For Atherosclerosismentioning
confidence: 99%
“…Noteworthy, some commonly used drugs with pleiotropic activity-that is, statins-are increasingly recognized as potential epigenetic drugs. 116…”
Section: Modification Of Inflammatory Pathways and Their Impact On At...mentioning
confidence: 99%
“…However, in the past, studies have shown that statins exhibit pleiotropic effects independent of their lipid-lowering properties. It has been reported that the epigenetic effects of statins mediate these pleiotropic effects, at least to some extent [ 4 ]. Among them, the anti-tumor properties of statins have attracted particular attention.…”
Section: Introductionmentioning
confidence: 99%